Modernisasi Lembaga Pendidikan Islam Di Indonesia - Rubai Misbahul, Dede; Auliani, Yasmin; Ulfah, Maria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The modernization of Islamic educational institutions has become a crucial issue in line with social change, scientific developments, and advances in digital technology. This study aims to examine the concept, direction, and practice of modernizing Islamic education through the reintegration of knowledge, renewal of thinking and learning methods, improvement of educational quality, and the role of Islamic education in facing the challenges of modernization. The study uses a qualitative approach through a literature review by analyzing scientific books, academic journals, and relevant documents. The results of the study indicate that the modernization of Islamic education is directed at unifying religious knowledge and general knowledge within a unified scientific framework, developing progressive and inclusive learning methods, improving teacher competency and adapting curriculum based on Islamic values, and strengthening digital literacy and Islamic ethics for students. Modernization practices in modern Islamic boarding schools (pesantren), science and technology-based Islamic schools, and Islamic community organizations demonstrate that educational reform can go hand in hand with the strengthening of Islamic identity. This study confirms that the modernization of Islamic education is an adaptive and sustainable process focused on developing a generation that is knowledgeable, moral, and plays an active role in modern society.